Acoustics and Sound Insulation : Principles, Planning, Examples - Mommertz, Eckard (DETAIL Practice, 2012)
Acoustics and protection against noise do not perhaps number among the primary parameters that normally influence the design of a building. Nevertheless, at the very latest when the lecturer in the seminar room cannot be heard, when the noise level in an open-plan office reaches unbearable levels, or when a neighbor's noise deprives you of sleep, it becomes clear just how essential acoustic can be to everyday well-being. it is not just concert halls or the amphitheaters of antiquity that call for acoustic quality; rather, every building, indeed every room, has an acoustic dimension that changes according to the nature of its particular requirements. This practice-oriented volume provides expert planners and architects but also interested developers with practical knowledge on the subject of acoustics in high-rise architecture, beginning with standards on methods of planning and prognosis and moving on to the areas of acoustics of rooms and architecture and noise protection in urban planning. Typologically organized chapters comment on proper approaches to the subject with examples of different types of building such as residential and office buildings, schools, kindergartens, lecture halls, event spaces, and so on, because appropriate acoustic conditions make an essential contribution to the success of a project.